Production of lactic acid from banana stem waste using mixed culture - Noor Azwani, Azhar (2014)
Lactic acid is a chemical compound that plays a role in various biochemical processes and also widely used in the food, cosmetic, pharmaceutical, and chemical industries. Lactic acid can be obtained by either microbial fermentation or chemical synthesis. Presently more than 95 % of industrial production of lactic acid is based on fermentation by using lactic acid bacteria. The research was done to produce lactic acid by using mixed culture of facultative anaerobic bacteria and banana stem waste. By using BSW as substrate and PMD as inoculums, the process was done according to selected factors. Source of inoculums (A), agitation (C) and ratio of substrate to inoculums (D) are categorical factors while temperature (B) and fermentation time (E) are numerical factors. Two factor A are used, Yakult and Nutrigen; three levels of factor B, 30, 35, 40 oC; agitate or non-agitate for factor C; while factor D used, 4:1 and 2:3; and also three levels of factor E, 20, 30, 40 hours. Design Expert 6.0 software is used to set the total number of experimental run, suggested validation experiment and also the best condition to produce lactic acid. The samples were analyzed using High Performance Liquid Chromatography while glucose content in the BSW is determined using Dinitrosalicylic Colorimetric (DNS) method and Ultra Violet-Visible (UV-Vis) Spectrometer. Factor A contributes the most in lactic acid fermentation with percentage of 1.07%. During preliminary experiments, Yakult and Nutrigen have respectively initial pH of 3.74 and 3.77 and decreases to 3.36 and 3.58 at the end of experiment. Previous study stated that when pH of the culture decreases, the concentration of lactic acid increases. Thus, it is showed that factor A could contribute the most in producing lactic acid. Factor‟s interaction between factor C and E contributes the most which is 35.55%. A total of five validation runs were suggested in order to confirm the experiment result. All runs have error between experimental and predicted lactic acid yield for about 8 – 35%. The best conditions to produce lactic acid for this research were at temperature 39oC, no agitation, 20 hours of fermentation time and only 8% error with predicted lactic acid yield of 0.1009 g/g and experimental lactic acid yield of 0.0925 g/g. The production of lactic acid is affected by glucose content in the substrate used, temperature, agitation and fermentation time. Utilization of total sugar increased as the fermentation time increased, reducing the available sugar content in the media, thus increasing lactic acid production. Therefore, the result obtained in the study showed that BSW can be used as substrate in producing lactic acid and the parameter tested does affect the production of lactic acid